Laparoscopic Myomectomy for the Removal of Large Uterine Myomas - Sano, Rikiya; Suzuki, Soichiro; Shiota, Mitsuru (The Surgery Journal, 2020)
Laparoscopic myomectomy (LM) is a minimally invasive surgery. However, several complications may occur in cases of extremely large myomas. For example, it can be difficult to acquire a full visual field, and the operation is limited by both technical and physiological restrictions. In addition, the volume of intraoperative bleeding is often increased in comparison to typically sized myomas; therefore, surgical indications are limited for technical reasons and for ensuring safety of the patient. Suturing and ligation techniques, which are indispensable in LM, are difficult procedures to perform. If clinicians are not confident in performing these procedures or experience difficulty in controlling bleeding, then they can alternatively choose to make a small incision in the abdominal wall and perform a procedure called laparoscopically assisted myomectomy.In this article, we describe the process of effectively using LM in cases with giant myomas.
Keywords: laparoscopic myomectomy; myomas; laparoscopic surgery; malignant tumor; surgical procedure; fibroids